Women and Modern Families: An Analysis of Quraish Shihab's Perspectives - Wahyuni, Tuty (Program Studi Aqidah dan Filsafat Islam, 2024)
In modern families, Islamic values are increasingly eroded due to the challenges posed by the advancement of information and communication technology. In contemporary Muslim families, wives often work outside the home but still serve as the primary educators within the family. This article aims to elucidate the concept of a harmonious family in the context of modern life, according to Quraish Shihab. The research employs a qualitative method with data collection techniques based on a literature review, examining Quraish Shihab's thoughts through his works from 1996 to 2022, encompassing ten books related to family issues. The findings reveal that Quraish Shihab places significant emphasis on the role of women and family. According to his works, including